Rekonstruksi Konsepsi Supply-side Tax Policy - ROSDIANA, HAULA (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2010)
Supply-side tax policy is generally identified with tax cut and other forms of tax incentives. Nevertheless, there are many other forms of tax policy that give larger space for private sectors to increase their productivity. It is this enlarged meaning and essence of supply-side tax policy that need to be reconstructed to hinder the policy from being trapped into tax incentive polemic. By understanding its philosophy, the concept of supply-side tax policy can be reconstructed through regulations and deregulations. Government should develop regulations on specific transactions unambiguously in order to minimize tax dispute. Simultaneously, cost of taxation for government and private sector will be reduced. The other available alternative is deregulation that will remove unfavorable tax provisions, i.e. those that create cost of taxation or cash flow distortion. This construction of supply-side tax policy is better than tax incentives since it neither intrude the government ability to generate revenue nor generate tax expenditure.